1996
DOI: 10.1039/p29960002119
|View full text |Cite
|
Sign up to set email alerts
|

Conformational, calorimetric and NMR spectroscopic studies on inclusion complexes of cyclodextrins with substituted phenyl and adamantane derivatives

Abstract: Inclusion modes in complexes with a-and byclodextrins in water have been investigated by NMR spectroscopy at 400 or 500 MHz, and compared with structures obtained by computer-aided molecular modelling and with calorimetric data. The NOEs observed on 0-and m-aryl protons upon irradiation of either H3 or H5 inside the CD cavity indicate for all phenols an inclusion mode with the hydroxy group at the wide cavity end, and an increasingly deep immersion for phenol or phenolate with iodine compared with this nitro g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 46 publications
3
86
0
3
Order By: Relevance
“…An alternative explanation is that both DDB environments involve insertion into the CD host, as it was previously shown that insertion of substituted phenyl compounds into CDs might give a mixture of two or more alternative forms. 42,43 Based on our experiments and previous studies, the observed kinetics for DDB in DDB/CMCD-LDH can be explained by a dynamic equilibrium between DDB molecules that are tightly bound to CMCD (with a relatively long fluorescence decay time) and those that are located near the exit of the hydrophobic cavity (with a relatively short fluorescence decay time).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative explanation is that both DDB environments involve insertion into the CD host, as it was previously shown that insertion of substituted phenyl compounds into CDs might give a mixture of two or more alternative forms. 42,43 Based on our experiments and previous studies, the observed kinetics for DDB in DDB/CMCD-LDH can be explained by a dynamic equilibrium between DDB molecules that are tightly bound to CMCD (with a relatively long fluorescence decay time) and those that are located near the exit of the hydrophobic cavity (with a relatively short fluorescence decay time).…”
Section: Resultsmentioning
confidence: 99%
“…Thus the variation of the shape, shift and intensity of the absorption peaks of the guest or host could provide enough information for the occurrence of the inclusion. 20 By comparison of IR spectra of gemfibrozil, β-CD, the physical mixture (gemfibrozil∶β-CD, 1∶1) of gemfibrozil and β-CD and the inclusion complex (Figure 6), it could be seen that the spectrum of c was essentially the combination of a and b, which indicated that physical mixture (gemfibrozil∶β-CD, 1∶1) could not lead to inclusion. There were apparent differences between the spectra of c and d and some characteristic IR absorption peaks of gemfibrozil and β-CD were changed obviously in inclusion complex: the benzene ring -C=C-bond stretching vibration absorption peak at 1600 cm -1 of gemfibrozil red-shifted to 1590 cm -1 ; the 1270 cm -1 absorption assigned to Ar-O red-shifted to 1230 cm -1 .…”
Section: Characterization Of β-Cd-gemfibrozil Inclusion Complex Ir Spmentioning
confidence: 96%
“…According to the partial 1 H NMR spectra of gemfibrozil, β-CD and the inclusion complex, apparent changes in chemical shifts of different protons could be observed ( Figure 7): compared with the dramatic upfield shifts of β-CD interior H-3, H-5 and H-6 protons, which resulted from the shielding effect exerted by the inclusion of gemfibrozil's benzene ring into β-CD cavity, the shifts of β-CD outside H-2 and H-4 protons could be neglected; the apparent shift changes of β-CD H-3 indicated that the guest molecule entered β-CD cavity along with its wide rim which possessed secondary hydrogens; 20 H-1, H-2 and H-3 of gemfibrozil benzene ring protons had dramatic chemical shift changes, otherwise other protons of gemfibrozil changed little. All of the changes showed that gemfibrozil benzene ring was included into the β-CD cavity and this was in good agreement with the results obtained from IR spectrum.…”
Section: H Nmr Spectrummentioning
confidence: 99%
“…[19] The upfield shift of the inner H3 and H5 protons of b-CD and downfield shift of the outer H2 and H4 protons from the free b-CD were observed as seen in the reported complexes between b-CD and the adamantane derivatives. [20,21] The formation of an inclusion complex was directly proved by the ROE correlation peaks between the inner protons of the b-CD and those of adamantane. As shown in many complexes between the b-CD and adamantane derivatives, [21] H3 showed stronger ROE cross-peaks with the proton of adamantane than H5 (Figure 4).…”
mentioning
confidence: 99%
“…[20,21] The formation of an inclusion complex was directly proved by the ROE correlation peaks between the inner protons of the b-CD and those of adamantane. As shown in many complexes between the b-CD and adamantane derivatives, [21] H3 showed stronger ROE cross-peaks with the proton of adamantane than H5 (Figure 4). Isothermal titration calorimetry (ITC) was used to confirm the affinity of the adamantane···b-CD interaction.…”
mentioning
confidence: 99%